Islamic Philanthropy and Optimization of ZISWAF as a Solution Overcoming the Economic Recession - Ahsani Taqwiem; Kartika Rose Rachmadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study focuses on the Islamic philanthropy movement and the optimization of ZISWAF conducted by LAZIS Sabilillah Malang City in an effort to overcome the economic recession in the city of Malang. Islamic philanthropy is an effort to alleviate poverty and empower the mustahiq economy through the provision of capital loans and business assistance. The purpose of this study is to analyze the effect of Islamic philanthropy variables and the optimization of ZIWAF on efforts to overcome the economic recession in Malang City through economic empowerment of business development and its implications for mustahiq through the utilization of zakat, infaq and shadaqah funds in LAZIS Sabilillah Malang City. The research methodology used in this research is research quantitative analysis tools with Smart PLS which aims to build a detailed view of the object of research by collecting information or symptoms that are happening now and then looking for solutions in solving the problem with a quantitative approach. The research design itself consists of two main activities, namely the data collection design and the sampling design. This study aims to determine the role of Islamic philanthropy that affects the optimization of ZISWAF against the economic recession in Malang City.From the results of this research, it can be found that the optimization of ZISWAFable to mediate the relationship of Islamic philanthropy programs carried out on the economic recession variable. Because the direct relationship between Islamic philanthropy and economic recession is significant, the optimization of ZISWAF mediates the relationship between Islamic philanthropy and partial mediation. The higher the ZISWAF optimization value obtained by mustahiq, the higher the success of overcoming the economic recession. the higher the Islamic philanthropy that exists and is obtained from mustahiq, the higher the success rate of overcoming the economic recession that is carried out. The higher the ZISWAF optimization obtained by mustahiq, the higher the success rate in overcoming the economic recession that is carried out.